Incentive compability of dual transfer pricing - Stefan Carstens; Michael Weinem (Universität-Gesamthochschule Essen, Fachbereich Wirtschaftswissenschaften, 2000)
We examine the implementation of efficient decisions about accepting a special order with asymmetric information by means of a dual transfer pricing mechanism based on Ronen and McKinney (1970). The model is designed in a simple fashion, two vertically related divisions within a firm (manufacturing and distribution) process a special order of a single product. Each division manager has private information about the divisional parameters (production costs and profit margin) and both report simultaneously to the other manager. The reports mutually affect the managers' payoffs by determining the transfer payments which are payed to both divisions. Subsequently, based on the reports, the principal decides if the special order will be accepted. The outcome of this model is that cheating is a Bayes-Nash equilibrium and is Pareto-efficient, but truth-telling is a dominant strategy incentive-compatible equilibrium and strongly risk-dominates cheating. When adding an additional stage to the game, the accounting stage, it becomes clear that the incentives are inverse to those in Ronen and McKinney (1970) as the incentives to cheat disappear. The reason is that the managers only receive the 'award' from cheating if they indicate the true information in the accounting stage. If they choose to report untruthfully then they suffer a loss as they need to pay the difference between the true and the incorrectly accounted value out of their own pocket. It follows that this model design is more robust against cheating than the introduction of a penalty, as studied by Ronen (1992). Therefore, dual transfer prices are able to implement the first-best solution. These results also clearly disprove the main results of Wagenhofer (1994).
Keywords: D82; M41; 330; agency theory; Bayes-Nash equilibrium; dual transfer pricing; incentive compatibility; risk dominance; Innerbetriebliche Leistungsverrechnung; Verrechnungspreis; Organisationsstruktur; Anreizvertrag; Prinzipal-Agent-Theorie; Behavioral Accounting; Spieltheorie; Theorie